2014
DOI: 10.1387/ijdb.140032kc
|View full text |Cite
|
Sign up to set email alerts
|

Uterine natural killer cells as modulators of the maternal-fetal vasculature

Abstract: Precise and local control of the innate immune system within the placenta is an essential component for achieving a normal and healthy pregnancy. One of the most abundant immune cells of the placenta is a subpopulation of natural killer (NK) cells that profusely populates the uterine decidua during early pregnancy. Uterine NK (uNK) cells and trophoblast cells of the placenta communicate both directly and indirectly to contribute to the critical process of spiral artery remodeling. Here, we discuss recent findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
0
13
0
1
Order By: Relevance
“…CD34 is a transmembrane protein expressed in hematopoietic progenitor cells, vascular endothelial cells, and embryonic fibroblasts (Wood et al, 1997). Restraint stress decreases the density of uterine natural killer (uNK) cells in the endometrium (Liu et al, 2014), and uNK cells directly or indirectly contribute to the critical process of maternal (Matson & Caron, 2014). Hence, the present study investigated whether the negative effect of restraint stress is exerted via impaired development of endometrial blood vessesl during embryo implantation.…”
Section: Introductionmentioning
confidence: 95%
“…CD34 is a transmembrane protein expressed in hematopoietic progenitor cells, vascular endothelial cells, and embryonic fibroblasts (Wood et al, 1997). Restraint stress decreases the density of uterine natural killer (uNK) cells in the endometrium (Liu et al, 2014), and uNK cells directly or indirectly contribute to the critical process of maternal (Matson & Caron, 2014). Hence, the present study investigated whether the negative effect of restraint stress is exerted via impaired development of endometrial blood vessesl during embryo implantation.…”
Section: Introductionmentioning
confidence: 95%
“…The arteries also lose their smooth muscle and become greatly dilated, a process known as spiral artery remodeling (Adamson et al, 2002). Cell ablation experiments have shown that SpA-TGCs are critical to initiate the remodeling (Hu and Cross, 2011), though the remodeling occurs well upstream of even the deepest invading SpA-TGCs (Adamson et al, 2002), and is thought to involve interactions with maternal uterine NK cells (Matson and Caron, 2014;Soares et al, 2014). The spiral arteries converge to form a large canal that carries oxygenated blood to the base of the placenta where it then enters the small sinusoid spaces within the labyrinth spaces lined by canal TGCs (C-TGC) and sinusoidal TGCs (S-TGC), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Remodeling of uterine spiral arteries, conduits of the uteroplacental circulation, is critical for proper placentation [5] and is accomplished in part by crosstalk between uterine natural killer (uNK) cells and trophoblast cells of the placenta [6]. Compared to wild type placentas, Adm -/- placentas exhibit fewer uNK cells and insufficient spiral artery remodeling [7].…”
Section: Introductionmentioning
confidence: 99%